Coming to my senses : one woman's cochlear implant journey - Blatchford, Claire H. (Gallaudet University Press, 2014)
"Deafened at the age of six, Claire Blatchford was educated orally with speech lessons, speechreading, and hearing aids. Though successful both professionally and domestically, at the age of 67 Blatchford decided to undergo a cochlear implantation. In this memoir, she describes in prose and verse living with a cochlear implant for the past three years. At first, Blatchford feared losing the last of her hearing through the surgical process. Her audiologist explained that her hearing was worsening and that soon she would move from profound deafness into a state called "cosmic deafness." Blatchford decided upon the surgery in hope of meeting her hearing family on their turf, and of again hearing the wind, rain, rivers, and crickets. After being implanted, however, she realized that amplification and comprehension were two different things: at first, all she heard was a soup of sound, a condition known as being brain deaf. Blatchford soon learned, however, that regaining her hearing was a journey of discovery. Gradually, the sound soup gave way to the ability to hear some sentences without speechreading. The sound of her own voice surprised her, and she could hear her grandchildren speak. The thrill of new things heard on one car trip to a friend's house moved her to "try my first yodel as I pass by your house." When asked by others if they should receive an implant, she cautions that it is an individual decision that each deaf person must make. For her, it was the right decision."--Publisher's description.